Sulfonated Hydrothermal Carbon-Based Catalyzed Esterification under Microwave Irradiation: Optimization and Kinetic Study - Laddawan Tumkot; Armando T. Quitain; Tetsuya Kida; Navadol Laosiripojana; Artiwan Shotipruk; Panatpong Boonnoun (Bulletin of Chemical Reaction Engineering & Catalysis, 2020)
In this study, the esterification reaction of oleic acid (OA) with methanol was investigated in the presence of a sulfonated hydrothermal carbon-based catalyst under microwave irradiation. The reaction conditions were optimized using response surface methodology based on a central composite design. Three following variables were studied: methanol to OA molar ratios (2.5:1–7.5:1), reaction time (50–70 min) and catalyst loading (2–5 wt.%) to provide a statistical model with the coefficient of regression (R2) of 0.9407. Based on the model, the optimum OA conversion of 95.6% was predicted at 5.8:1 methanol to OA molar ratio, 60 min and 3.05 wt.% catalyst loading. The experimental validation indicated that the model gave a good prediction of OA conversion (2.8% error). Furthermore, the reaction was found to be reasonably described by the pseudo-first order kinetics. The dependency of the reaction rate constant on temperatures gave a value of the activation energy of 64 kJ/mol. Copyright © 2020 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).